The effect of tax planning and profitability on firm value: A study of manufacturing companies in the industrial goods subsector - Tania Ananta Dewi; Edi Jaenudin; Ken Paramitha Aryana (Educoretax, 2026)
This study aims to analyze the impact of tax planning and profitability on the firm value of manufacturing companies in the industrial goods sub-sector listed on the Indonesia Stock Exchange during the 2021–2024 period. The research is motivated by fluctuations in firm value, which are influenced by a company's ability to manage tax obligations and generate profits amidst changing tax policies during the economic recovery phase. Tax planning is proxied by the Effective Tax Rate (ETR), profitability by Return on Assets (ROA), and firm value by Price to Book Value (PBV). This study employs a quantitative approach using secondary data obtained from annual financial reports. The sample was selected using a purposive sampling technique, resulting in 15 companies and a total of 60 observations. Data analysis was conducted using panel data regression via Eviews 14, with the Random Effect Model (REM) identified as the best-fit model. The findings indicate that both tax planning and profitability individually exert a significant positive influence on firm value. Furthermore, the two variables simultaneously exert a significant influence on firm value, with an Adjusted R-Squared value of 54.24%, indicating that tax planning and profitability collectively explain 54.24% of the variation in firm value.